EFEKTIVITAS MODEL PEMBELAJARAN DISCOVERY LEARNING DAN PROBLEM BASED LEARNING TERHADAP KEMANDIRIAN BELAJAR IPAS SISWA KELAS IV SEKOLAH DASAR - Panjalu, Jonathan Budi; Winanto, Adi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to determine the difference in the effectiveness of the Discovery Learning and Problem Based Learning learning models on student learning independence in grade IV elementary school science subjects. Learning independence is defined as a student's ability to manage, direct and control the learning process independently, including initiative, sense of responsibility, self-confidence, discipline, self-management, self-direction, self-control. The research method used was an experiment with a nonequivalent control group design, involving two groups, one using the Problem Based Learning (PBL) model while one group using Discovery Learning (DL). Data was collected through observation and learning independence questionnaires. Data analysis was carried out by testing differences in learning independence after taking action with the PBL and DL learning models. The research results show that there are differences in learning independence between the two models.